Teaching Motivation And Job Satisfaction Of First School Teachers In Indonesia: A Reference For Future Career Development Training - Ristiyola, Ristiyola; S. Sicat, Alvin (Universitas Ibn Khladun Bogor, 2025)
This study examines the levels of teaching motivation and job satisfaction among first-year school teachers in Indonesia, highlighting their implications for future career development training. Using a mixed-method design, the research gathered data from 400 primary school teachers across various provinces through structured questionnaires and open-ended responses. Quantitative data were analyzed using descriptive statistics, ANOVA, and t-tests, while qualitative data underwent thematic analysis. Results indicate that both motivation (mean = 3.45) and job satisfaction (mean = 3.38) were at moderate to high levels. Professional commitment, confidence, and goal orientation emerged as the most influential motivational factors, whereas compensation and benefits received the lowest ratings. Significant differences were found across teacher demographics, particularly in terms of age, experience, and educational attainment. Qualitative findings highlighted the need for recognition, mentorship, and relief from administrative burdens. The study concludes that while intrinsic motivation remains strong, systemic barriers—especially inadequate compensation and bureaucratic workload—continue to suppress overall satisfaction. It recommends demographic-responsive career development programs focused on stress management, pedagogical advancement, and work-life balance to enhance teacher performance and retention.